ANALISIS PROFITABIITAS DALAM MENILAI KINERJA KEUANGAN UMKM JASA STUDIO KITA PESERTA PROGRAM MAHASISWA WIRAUSAHA (PMW) POLITEKNIK NEGERI BATAM - Hati, Shinta Wahyu; Ningrum, Selvy Agita (IQTISHODUNA, 2015)
Studio Kita is a company in the scale of SMEs. It is a company owned by student a participant of theStudent Entrepreneurial Program (Program Mahasiswa Wirausaha) Politkenik Negeri Batam. The purpose ofthis study is 1) to determine the level of financial performance by using the ratio of profitability. 2). todetermine the effect of the productivity ratio analysis in the Companyâ€™s profitability. Based on the calculationand analysis of profitability ratios period October 2013 to February 2014 the Companyâ€™s financial performanceof Studio Kita show that the state is not good enough or not efficient because it tends to decrease very large,while based on the calculation and analysis of the ratio according to the Regulation of the Minister ofCooperatives and SMEs Republic Indonesia Number 06/Per/M.KUKM/V/2006 the company in the categoryof â€unhealthyâ€. Based on the analysis of profitability ratios that have been made to the Companyâ€™s financialstatements Studio Kita from the period October 2013 to February 2014, it can be concluded that the companyby using its profitability will determine the ability to generate profits and these profits will be the size of thedevelopment of enterprise productivity that can help companies to improve its performance and productivity.